1996
DOI: 10.1056/nejm199602293340902
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Hepatitis C Virus by a Cardiac Surgeon

Abstract: Our findings provide evidence that a cardiac surgeon with chronic hepatitis C may have transmitted HCV to five of his patients during open-heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
0
18

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(146 citation statements)
references
References 32 publications
2
126
0
18
Order By: Relevance
“…As seen in this study, HCV infection can progress rapidly to cirrhosis in immunocompromised patients, such as liver transplant recipients. Except in the rare event in which an HCV-infected health care worker is the source of infection or in cases of circumscribed epidemics, 5,7 demonstration of the mechanism of nosocomial HCV transmission is extremely difficult. Nevertheless, acquisition of HCV infection in the hospital setting can generate long and expensive legal claims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in this study, HCV infection can progress rapidly to cirrhosis in immunocompromised patients, such as liver transplant recipients. Except in the rare event in which an HCV-infected health care worker is the source of infection or in cases of circumscribed epidemics, 5,7 demonstration of the mechanism of nosocomial HCV transmission is extremely difficult. Nevertheless, acquisition of HCV infection in the hospital setting can generate long and expensive legal claims.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Transmission of HCV by an infected health care worker is a very rare event and has been essentially linked to surgery or medical care. 7,8 Although health care-related procedures have not been unequivocally associated with HCV acquisition in case-control studies, 2 some studies have demonstrated a higher prevalence of HCV infection in patients who underwent invasive medical procedures or prolonged hospitalization. 9,10 Transmission of HCV in hemodialysis and hematology units is well documented.…”
mentioning
confidence: 99%
“…To date there have been three reported instances of HCW to patient transmission of HCV, [31][32][33] none of which were in dentistry, suggesting that the risk of transmission from HCW to patient is low. Based on this evidence, the UK Advisory Group on Hepatitis are recommending that HCWs with hepatitis C infection are not prevented from performing EPPs unless they have already been shown to transmit hepatitis C, but this advice is kept under constant review.…”
Section: Work Practices For Hcws Infected With Hcvmentioning
confidence: 99%
“…Tereskerz, R.D. Pearson, and J. Jagger Morgan, et al 1992;Johnston, MacDonald, Lee, et al 1992;Heptonstall, Collins, Smith, et al 1994;Harpaz, Von Seidlein, Averhoff, et al 1996;Hospital Employee Health 1996;Incident Investigation Teams and Others 1997), HCV (Esteban, Gomez, Martell, et al 1996;Bosch 1998), and HIV (Lot, Seguier, Fegeux, et al 1999) from physicians to patients during invasive procedures have again raised the question of whether it is advisable for physicians infected with these types of dangerous or lethal bloodborne pathogens to perform invasive procedures, and, if so, under what conditions.…”
mentioning
confidence: 99%
“…Patients of an HCV-positive cardiac surgeon have been infected with that virus (Esteban et al 1996). More recently, an HCV outbreak reported in Spain was traced to an anesthetist with the same HCV genome as the infected patients (Bosch 1998).…”
mentioning
confidence: 99%